Qualidade fisiológica e sanitária de sementes de feijoeiro (Phaseolus vulgaris L.) provenientes do estado de Goiás - Silva, Gilvânia Campos; Gomes, Delineide Pereira [UNESP]; Kronka, Adriana Zanin [UNESP]; Moraes, Myrna Hilal (Universidade Estadual de Londrina, 2008)
The common beans (Phaseolus vulgaris L.) is a fabacea sufficiently spread out in all domestic territory. However, the quality of its seeds represents one of the main causes of low productivity in the beans farmings in Brazil. The objective of this work was to evaluate physiological and sanitary seed qualities of eleven bean cultivars. The physiological seed quality was evaluated trough standard germination and vigor tests. The sanitary seed quality was evaluated through two tests: blotter test was employed to evaluate fungi incidence and Koch & Menten method was employed to observe Sclerotinia sclerotiorum (Lib) de Bary occurrence. Xamego, BRS Valente, Bambu and Pérola had the best results of physiological tests. Jalo Precoce, Roxo 90, Corrente and Aporé had no good results of vigor and germination, besides presenting the lowest indices of died seeds. Fusarium sp., Aspergillus spp., Penicillium sp., Phoma sp., Rhizopus sp. and Botrytis sp. were the fungi detected in the sanity tests.
Physiological and sanity seed quality of common beans (Phaseolus vulgaris L.) from Goias state
Keywords: Germination; Seed pathology; Vigor